KONFLIK TOKOH DALAM NOVEL MARVELUNA KARYA ITA KRN - Wa Ode Azizah; Sumiman Udu; La Tike (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The problem of this research is what is meant by conflict between characters in the novel Marveluna by Ita Krn? This research aims to describe the conflict between characters in the novel Marveluna by Ita Krn. One of the benefits is as reference material for further research, especially character conflicts in a novel. This research method is descriptive qualitative. This research is referred to as library research. The data source in this research is a novel entitled Marveluna by Ita Krn published by Kawah Media, Jakarta, 2022 with a thickness of 332 pages. The technique used to collect data in this research is analytical reading techniques. Data analysis techniques This research uses a structural approach. Based on the research results, it was concluded that the conflict contained in the novel Marveluna by Ita Krn is in the form of internal conflict and external conflict. Meanwhile, internal conflict is the inner conflict experienced by the characters in the novel Marveluna. while external conflict is the physical conflict experienced by the characters in the novel Marveluna by Ita Krn.